An experimental and numerical investigation on a paraffin wax/graphene oxide/carbon nanotubes composite material for solar thermal storage applications. (15th April 2020) - Chen, Guijun; Su, Yunpeng; Jiang, Dongyue; Pan, Lujun; Li, Shuai
Graphical abstract: Highlights: The thermal conductivity of the composite phase change material is 0.46 W m −1 K −1 . The composite phase change material contains only 2.2 wt% of hybrid graphene aerogel. The solar absorptance of the composite phase change material is 0.952. The composite phase change material has the advantages of good shape stability. The light-to-heat efficiency of collector is 27% by numeral simulation. Abstract: In this study, a composite phase change material (PCM) with hybrid graphene aerogel (HGA) composed of graphene oxide (GO) and carbon nanotubes (CNTs), as well as paraffin wax (PW) is prepared. In the composite PCM, the graphene aerogel plays a role as a skeletal structure to seal the PW, and provides more pathways for thermal conduction. The CNTs perform as extended surface on the skeletal structure for a further improvement of the thermal conductivity. The prepared composite PCM with 2.2 wt% of HGA exhibits a thermal conductivity as high as 0.46 W m −1 K −1, 1.77-fold higher than that of pure PW (0.26 W m −1 K −1 ), and 1.44-fold higher than the PW/GA composite PCM. At the same time, the prepared composite PCM also possesses a large solar absorptance (close to 1) in the solar spectrum, which is 1.4-fold higher than that of pure PW. In addition, owing to the low density of HGA, the composite PCM reveals a comparable heat storage performance as compared to pure PW. In addition, the feasibility of composite PCMs in a solar thermal storage system is modelled and studied by numerical simulation. The results indicate that the numerical model could predict the solar thermal storage process accurately. The PW/G2C1-CA solar unglazed collector shows good performance in terms of large solar energy storage and short charging/discharging durations.